2021
DOI: 10.3390/biomedicines9101425
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Uterine Natural Killer Cells on Recurrent Miscarriage and Recurrent Implantation Failure: From Pathophysiology to Treatment

Abstract: Uterine natural killer (uNK) cells constitute a unique uterine leucocyte subpopulation facilitating implantation and maintaining pregnancy. Herein, we critically analyze current evidence regarding the role of uNK cells in the events entailed in recurrent implantation failure (RIF) and recurrent miscarriages (RM). Data suggest an association between RIF and RM with abnormally elevated uNK cells’ numbers, as well as with a defective biological activity leading to cytotoxicity. However, other studies do not concu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 120 publications
0
19
0
Order By: Relevance
“…Expression of NFKB1 , NFKB2 , REL , RELA , interleukins ( IL1B , IL2 , IL18 ), INFG , CCL2 , CXCL1 , and CXCL10 is increased in the endometria of the pathology group. NFκB is involved in signaling by modulating DNA transcription, thereby regulating essential immune responses [ 36 ]. Studies show that during implantation, the expression and secretion of inflammatory mediators, such as IFNG and IFND, PGF2α and PGE2, TNFA, IL1B, IL6, IL11, and LIF are increased by the endometrium [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Expression of NFKB1 , NFKB2 , REL , RELA , interleukins ( IL1B , IL2 , IL18 ), INFG , CCL2 , CXCL1 , and CXCL10 is increased in the endometria of the pathology group. NFκB is involved in signaling by modulating DNA transcription, thereby regulating essential immune responses [ 36 ]. Studies show that during implantation, the expression and secretion of inflammatory mediators, such as IFNG and IFND, PGF2α and PGE2, TNFA, IL1B, IL6, IL11, and LIF are increased by the endometrium [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The pro-inflammatory Th1 cell subtype secretes cytokines such as interferon-gamma (IFNγ), tumor necrosis factor-alpha (TNF-α), and interleukins IL-1, 2, 12, 15, and 18, whereas the Th2 subtype secrets anti-inflammatory cytokines, namely IL-4, 5, 6, 10, and 13 as well as granulocyte-macrophage colony-stimulating factor (GM-CSF) [26,46,48,49]. Moreover, uNK cells stand as a category of NK cells that reside in the uterus and dominate in the secretory endometrium as well as during early pregnancy decidua [51,52]. Besides the cytolytic nature characterizing uNK cells, these cells also possess an additional function being a source of cytokines in the endometrium [43,45,52].…”
Section: Basic Immunological Characteristics Of the Endometrial Micro...mentioning
confidence: 99%
“…Moreover, uNK cells stand as a category of NK cells that reside in the uterus and dominate in the secretory endometrium as well as during early pregnancy decidua [51,52]. Besides the cytolytic nature characterizing uNK cells, these cells also possess an additional function being a source of cytokines in the endometrium [43,45,52]. Lastly, the macrophages participate in trophoblast invasion, tissue and vascular remodeling, and are divided into activated and alternatively activated macrophages.…”
Section: Basic Immunological Characteristics Of the Endometrial Micro...mentioning
confidence: 99%
“…Thus, multiple tentative immunotherapeutic approaches/drugs designed to reduce the activity of NK cells, such as lymphocyte immunotherapy (LIT), intralipid therapy and injection of tumor necrosis factor alpha (TNFα) inhibitors/immunoglobulins (IVIg)/steroids/glucocorticoids/G-CSF, have been applied to treat RM or recurrent implantation failure (RIF) clinically, which have been comprehensively reviewed and critically analyzed in previous literatures ( 179 181 ). In general, there is no uniform evidence that the above-mentioned immunotherapeutic approaches benefit clinical outcomes in patients; and there is no consensus on the role of uNK cells in RM or RIF ( 180 ). However, recent studies have shown that uNK cells have special physiological functions in reproduction, especially in the establishment and maintenance of pregnancy ( 182 , 183 ), and corticosteroids/intralipid therapy that suppress NK cells activity may exacerbate pregnancy failure ( 184 , 185 ).…”
Section: Potential Of Unk Cells In Treating Reproductive Diseasesmentioning
confidence: 99%